OFR-65-84 Geochemical Properties And Toxicological Effects On Aquatic Life Of Coal Wastes - William R. Roy (The National Institute for Occupational Safety and Health (NIOSH), 1984)
Seven coal-related waste samples (mining, cleaning, and gasification) were characterized chemically and mineralogically. Laboratory extracts of each sample, using a variety of different extraction methods, were used in both acute and chronic bioassays. A coal slurry sample (coarse fraction) and two coal cleaning refuse samples were chemically and mineralogically similar, and generated acidic water-waste systems, both in the laboratory and in the field. Acidic laboratory extracts and field samples of acid mine drainage in the area where the solid samples were collected, tended to be in equilibrium with some type of CaSO4 phase and with maghemite. The chemical composition of the extracts was sensitive to the method used to generate the extracts, but generally had the same prevalent chemical character as the field samples. The acidic wastes contain appreciable quantities of soluble Al, Mn, Ni, SO4, and Zn as indicated by both laboratory extraction and field data. Long-term extractions suggest that some constituents (Al, Fe, SO4) continued to be released by the acidic wastes after 22 weeks with no apparent associated change in pH. Two mine spoil samples, essentially shale, tended to generate water-waste systems that were neutral in pH and consequently released lower quantities tit potential pollutants than the acid wastes. The gasification residue was compositionally similar to coal-fired power plant slag and fly ash and generated moderately alkaline extracts with low concentration of soluble potentially toxic constituents. All of the solid wastes contained a variety of organic compounds, many of which are on the EPA Priority Pollutant List. However, these compounds were essentially insoluble in aqueous media. Each extract was tested for acute toxicity with tour species of freshwater aquatic organisms; green sunfish (Lepomis cyanellus), fathead minnow (Pimephales promelas), a crustacean (Daphnia magna), and a snail (Physa anatina). The extracts of the two mine spoil samples and of the gasification residue were not toxic to any of the organisms while the extracts from the acidic refuse and slurry samples were acutely toxic to all of the organisms. For all cases, pH was significantly correlated to mortality while Al, Fe, Mn, Ni, and Zn were significantly correlated to mortality in specific instances. Data from 96-hour LC-50 determinations showed that dilutions up to 1:1000 were necessary to eliminate mortality. The most toxic extracts were those with the lowest pH which necessitated the largest amounts of dilution to eliminate mortality. Chronic bioassays with the same test organisms were investigated with leachate samples from a relatively unweathered refuse sample and an older, more weathered refuse sample. The unweathered refuse sample generated a leachate that was acutely toxic while the leachate from the weathered refuse sample was not acutely toxic. No detrimental chronic effects were noted in organisms exposed to dilutions of the non-toxic leachate while low concentrations of the acutely toxic leachate produced lower hatchability for the Lepomis cyanellus and Pimephales promelas eggs, increased mortality with chronic exposure for Lepomis cyanellus, Daphnia, Physa, and reduced weight gain for Physa. Dilutions of a toxic, high-Fe leachate resulted in the precipitation of ferric hydroxide that was implicated as the major causative factor accounting for the physical and physiological toxic effects exhibited by all of the test organisms in these acutely sublethal concentrations. The toxicity of this leachate demonstrates the potential effects that these types of wastes can have on the aquatic ecosystem if they enter a receiving water in a natural setting.